Indigenous Healing Practices among Mothers in the Rural Areas of Pilar: an Alternative Health Care During Covid 19 - Obligar, Philomel Innocent; Dayal, Elizabeth; Contretas, Eric Esteban (International Journal of Applied Research and Sustainable Sciences, 2024)
Since the advent of modern medicine, indigenous healing methods have been used in rural areas. Mothers have a significant rule on family’s health decision-making, they often manage diseases by keeping an eye on symptoms, researching potential causes, and weighing the family's financial burden before seeking medical assistance. This study aimed to find out the indigenous healing practices among women’s in the rural areas of Pilar, Capiz which aims to find out the socio-demographic profile of the respondents; determine the common illnesses respondents family experienced; and determine the indigenous healing practices they used in treating such illnesses. The researchers used descriptive type of research conducted in 6 barangays in the Municipality of Pilar. 1087 women serves as respondents of the study selected through stratified sampling technique. Percentage and frequency were the statistical tools used in analysing the data. Result revealed that seventeen (17) common illnesses were experienced by the respondents. Cough, headache, body pain, parasitic infection and diarrhea were the top 5 common illnesses they have experienced. The respondents practice seven (7) indigenous healing techniques.